SÍNTESE E CARACTERIZAÇÃO DE PÓS CERÂMICOS COM COMPOSIÇÃO LaCr0,5Ni0,5O3 BASEADO NO MÉTODO PECHINI PARA ÂNODO DE CÉLULAS A COMBUSTÍVEL DE ÓXIDO SÓLIDO - Wendler, Leonardo Pacheco (2014)
The solid oxide fuel cells (SOFCs) have been considered as one of the most promising power sources to the future, and because that have awakened the interest from the governments and large companies. The large scale utilization of these devices only depends on costs reduction and better systems performance. The anode is one of the most requested components of a SOFC, because maintains direct contact with the fuel. The anode material must presents thermal stability, compatibility with the electrolyte, good catalytic activity and electronic conductivity. A lot of materials have just tested for use as SOFCs anodes, including metals like platinum and nickel. However, many problems were found, mainly because platinum wasn´t able to maintain its integrity in the cell operation conditions, suffering peeling during the process; and nickel particles suffered sintering in the high operation temperatures of the cell, blocking the fuel arrival to reaction sites, causing the loss of system performance. One of the alternatives to these metals are the lanthanumcontaining materials with perovskite structure. To this study it has been proposed the utilization of a lanthanum-based perovskite containing chromium, which provides good stability, and nickel, which provides good catalytic activity. Thus, the aim of the present study is to obtain the perovskite structure LaCr0,5Ni0,5O3, and characterize it to verify if its properties place it like a possible material to utilization as SOFC anode. It was investigated the obtaining of this composition by Pechini method, and the samples were characterized by X-ray diffraction, infrared spectroscopy, thermo gravimetric analysis, differential thermal analysis, He picnometry, specific surface area by BET method, scanning electronic microscopy, energy dispersive X-ray spectrometry, impedance spectroscopy and mercury porosimetry. The synthesized material showed high electrical conductivity at room temperature, and showed potential for use as anode in SOFCs.